2015
DOI: 10.1016/j.brainres.2014.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inactivation of the prelimbic cortex emulates compulsive reward seeking in rats

Abstract: Drug addiction is a chronic, relapsing brain disorder characterized by compulsive drug use. Contemporary addiction theories state that loss of control over drug use is mediated by a combination of several processes, including a transition from goal-directed to habitual forms of drug seeking and taking, and a breakdown of the prefrontally-mediated cognitive control over drug intake. In recent years, substantial progress has been made in the modelling of loss of control over drug use in animal models, but the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 68 publications
4
33
0
Order By: Relevance
“…On the one hand, these negative findings concur with recent work showing that pharmacologically inactivating the rat dmPFC did not affect punished EtOH lever pressing (55) or conditioned avoidance behavior (62). On the other hand, a lack of dmPFC silencing effects is perhaps surprising in view of the neural correlates of probe performance we detected in the dmPFC, as well as earlier data from rats showing that dmPFC inactivation or photosilencing increased punished licking for water (63) and promoted punished cocaine seeking (64,65).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the one hand, these negative findings concur with recent work showing that pharmacologically inactivating the rat dmPFC did not affect punished EtOH lever pressing (55) or conditioned avoidance behavior (62). On the other hand, a lack of dmPFC silencing effects is perhaps surprising in view of the neural correlates of probe performance we detected in the dmPFC, as well as earlier data from rats showing that dmPFC inactivation or photosilencing increased punished licking for water (63) and promoted punished cocaine seeking (64,65).…”
Section: Discussionsupporting
confidence: 90%
“…Punished Suppression of EtOH-SA Produces vmPFC/NAc Plasticity Our next step was to identify vmPFC outputs that modulate punished suppression, focusing on the NAcS. We tested for plastic changes to synaptic inputs selectively from the vmPFC to NAcS associated with punished EtOH-SA, focusing on D1-MSNs, given the cell specificity of EtOH-induced changes described in the introduction and the report that pharmacologically blocking D 1 receptors in the NAcS promotes EtOH-(and sucrose) SA elicited by conditioned cues/contexts (25,(61)(62)(63)(64)(65). Indeed, fluorescence in situ hybridization labeling of fos and messenger RNA markers for D 1 and D 2 receptorexpressing neuronal phenotypes showed that the large majority of probe testing-activated (fos-positive) NAcS MSNs were D 1 receptor-expressing (Supplemental Figure S5).…”
Section: Punishment and The Prefrontal Cortexmentioning
confidence: 99%
“…Contemporary addiction theories implicate the cognitive control over drug intake, value‐based decision making and impulse control are synergistically mediated by the frontal cortex (Limpens et al . ). Taken together with the present findings, in the context of human behaviour, it is possible that mitragynine‐induced impairment at these regions contributes to ineffective decision making in complex situations involving positive/negative consequences, eventually leading to compulsive aspects of kratom use.…”
Section: Discussionmentioning
confidence: 97%
“…We, and others, have previously shown that prolonged exposure to self‐administered cocaine results in compulsive, addiction‐like patterns of behaviour (Deroche‐Gamonet et al ; Vanderschuren & Everitt ; Pelloux, Everitt, & Dickinson ; Limpens et al ). Recent studies have implicated functional changes in VS (Kasanetz et al ; Bock et al ), DS (Zapata et al ; Jonkman et al ) and mPFC (Chen et al ; Kasanetz et al ; Limpens et al ) in this behaviour. In view of these findings, it is remarkable that we observed no major differences in IEG responsivity patterns in these brain regions between animals with 10 and 60 days of cocaine self‐administration experience.…”
Section: Discussionmentioning
confidence: 99%